Women's Rights Limitation In Stephen King's 'Sleeping Beauties' (2017) - Riski Aprinaldo; Desvalini Anwar (English Language and Literature, 2022)
This research is an analysis of the novel Sleeping Beauties  (2017) by Stephen king. The purpose of this study is to reveal   the issue of limitations women’s rights experienced by the women characters in the novel Sleeping Beauties (2017). This study uses Iris Yong’s  five forms of oppression (1990) to  reveal  rights limitations through the oppression that has been done on the women characters. As a result the female characters in this novel experience rights restriction as a woman as the results of  the marginalization, violence and exploitation acted on them.